1997
DOI: 10.1002/(sici)1097-0215(19970729)72:3<389::aid-ijc2>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and the risk of brain tumors: A population‐based study in Sweden

Abstract: Possible associations between childbearing and the risk of brain cancer were explored in a case-control study ''nested'' within a large nationwide cohort defined by the Swedish Fertility Registry. Among women born between 1925-1975, 1,088 patients with meningiomas and 1,657 patients with gliomas were identified in the Swedish Cancer Registry. For every woman diagnosed with brain tumor, 5 age-matched controls were selected among those in the Fertility Registry. Relative risks were estimated by odds ratios from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…These findings differ from a population-based study restricted to rural women in the upper Midwestern States (N=341 cases) which reported an elevated odds ratio (OR = 1.22 95% CI: 0.77–1.96) with ever giving birth and gliomas 15. Our results of no association with increasing number of children agree with most, but not all,12,19 previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings differ from a population-based study restricted to rural women in the upper Midwestern States (N=341 cases) which reported an elevated odds ratio (OR = 1.22 95% CI: 0.77–1.96) with ever giving birth and gliomas 15. Our results of no association with increasing number of children agree with most, but not all,12,19 previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Four of six studies reported parous women were at reduced risk of gliomas compared with nulliparous women. In the largest population based case control study to date (N=1657 glioma cases), Lambe et al reported a 24% reduced risk in ever parous Swedish women compared to nulliparous women (OR = 0.76 95% CI: 0.66–0.87) 12. A more recent but smaller hospital based case control study found similar, but non-significant, results (OR = 0.85 95% CI: 0.54 – 1.35),19 whereas odds ratio for parity were near the null in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,29,32,33 In these studies the researchers found no significant relationship between meningioma risk and number of pregnancies. Although three of these studies comprised relatively few cases, the fourth, which was conducted within the Swedish Fertility Registry, was composed of more than 1000 cases with five age-matched controls.…”
Section: Discussionmentioning
confidence: 91%
“…This could potentially explain the higher incidence in women with higher education. Hormonal and reproductive differences between the two sexes could also potentially explain the difference in incidence of meningioma and glioma between men and women 18 20 21…”
Section: Discussionmentioning
confidence: 99%